Uso de Sistemas Agrivoltáicos para Geração de Renda em Áreas Susceptíveis a Desertificação. - Carvalho, Gabriel Marçal da Cunha Pereira (2023)
Solar photovoltaic energy has been growing in Brazil, especially in Ceará State, driven by cost reduction and the interest of the agricultural and livestock sectors. Agrivoltaic systems combine agriculture and solar energy, bringing benefits such as additional income generation, reduction of CO2 emissions, and recovery of degraded areas susceptible to desertification. This approach integrates food production and renewable energy, contributing to a fair energy transition. The proposed Agrivoltaic system uses a crop adapted to the caatinga (cowpea), rainwater harvesting, and carbon emission reduction. Along with the system’s implementation, it is suggested to implement a state program that will generate income to lift the beneficiaries out of poverty. The case study shows that it is feasible to generate over R$ 1,345 Brazilian Reais monthly for a four-resident family located in Moraújo, Ceará, with an 88 kWp Agrivoltaic system. In an expanded program scenario, it is noted that it would be possible to carry out 494 projects of the same size with an initial investment of R$ 262.7 million Brazilian Reais.